ANALISIS PERBUATAN MELAWAN HUKUM KOMISI PEMILIHAN UMUM - Sadat, Anwar; Razikin; Putra, Nandio Rafael Aryo; Mawahid, Syamsul; Sugito; Novita, Wiliana Dian (The Juris, 2024)
This research is legal research with an analytical study of the Unlawful Acts of the General Election Commission (Onrechtmatige Overheisdaad) in Court Decision Number 757/Pdt.G/2022/Pn Jkt.Pst. The purpose of this study is to determine the absolute competence of the District Court to try the unlawful acts of the General Election Commission and to analyze the basis for the judge's considerations in granting the Prima party's lawsuit. The method used in this study is normative legal research. This study found that the absolute competence of the Court to try the Unlawful Acts committed by the KPU should be the domain of the State Administrative Court, not the State Court, so that in the context of the KPU vs. Prima Party case there was an error in applying the law. In the considerations of the Central Jakarta District Court Judge who Granted the Application for the Prima Party's Unlawful Acts Lawsuit carried out by the General Election Commission of the Republic of Indonesia in the District Court Decision Number: 757/Pdt.G/2022/Pn. Jkt Pst the panel of judges did not clearly explain what and how the considerations of the decision stating that the District Court has the authority to try the lawsuit filed by the PRIMA Party in issuing an interim decision.